Towards Artistic Education with Textiles: a sustainable challenge with K10 children - Duarte de Almeida, I.; M.J. Delgado (1st International Conference in Textiles, Identity and Innovation - D_TEX Textile Design Conference, 2017)
Making art with textiles has become part of the development process of creative potential that has led to the acquisition of different types of skills strongly correlated to the success of the textile and clothing industry. There are objectives defined in the curricula of basic education and pre-school education (K10 children) that tackle the artisanal process of transforming raw textile materials: these include acquiring knowledge of textile materials, highlighting the importance of handicrafts in culture and heritage, textile arts and the development of fine motor skills. The objective of this study is to learn about the practices of K10 children using textiles in schools, and to understand how these practices contribute to the development of their creative potential with regard to the area of textiles and clothing. Integrating the activities with textiles makes sensitization to the ma-terials and techniques of the textile arts possible, and paves the way for greater sustainability of this sector in Portuguese society.